2008
DOI: 10.1007/s00535-008-2249-7
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of pancreatic fibrosis and applications to the treatment of chronic pancreatitis

Abstract: Pancreatic stellate cells (PSCs) play a crucial role in pancreatic fibrogenesis in chronic pancreatitis and in the desmoplastic reaction of pancreatic cancer. When PSCs are stimulated by oxidative stress, ethanol and its metabolite acetaldehyde, and cytokines, the phenotype of quiescent fat-storing cells converts to myofibroblastlike activated PSCs, which then produce extracellular matrix, adhesion molecules, and various chemokines in response to cytokines and growth factors. Recent data suggest that PSCs have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
73
0
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(85 citation statements)
references
References 85 publications
(87 reference statements)
7
73
0
5
Order By: Relevance
“…The tumor microenvironment or desmoplastic stroma in PDAC is home to many cellular and molecular components. Reciprocal growth factor signaling results in strong expression of growth factors such as transforming growth factor (TGF)-β, platelet-derived growth factor (PDGF), and epidermal growth factor (EGF) (20). Impaired paracrine signaling between CAFs and cancer cells and alterations in the ECM microenvironment caused by depletion of CAFs may directly contribute to changes in cancer cells, leading to acquisition of epithelialmesenchymal transition (EMT), a stem cell-like phenotype, and dedifferentiation.…”
Section: α-Smooth Muscle Actin (αSma) Expression According To Treatmementioning
confidence: 99%
“…The tumor microenvironment or desmoplastic stroma in PDAC is home to many cellular and molecular components. Reciprocal growth factor signaling results in strong expression of growth factors such as transforming growth factor (TGF)-β, platelet-derived growth factor (PDGF), and epidermal growth factor (EGF) (20). Impaired paracrine signaling between CAFs and cancer cells and alterations in the ECM microenvironment caused by depletion of CAFs may directly contribute to changes in cancer cells, leading to acquisition of epithelialmesenchymal transition (EMT), a stem cell-like phenotype, and dedifferentiation.…”
Section: α-Smooth Muscle Actin (αSma) Expression According To Treatmementioning
confidence: 99%
“…Fibrogenesis is also associated with activation of pancreatic stellate cells (PSCs). It has been reported that PDGF and TGF-β1 play key roles in PSC-mediated pancreatic fibrogenesis through autocrine and paracrine loops [75][76][77]. In the early stage of pancreatic damage, quiescent PSCs undergo a transformation into α-SMA expressing myofibroblast-like cells, which then produce extracellular matrix leading to proliferation and collagen production [78].…”
Section: Pancreatic Fibrosismentioning
confidence: 99%
“…Despite this fact, data from animal studies have shown that acetaldehyde by itself does not elicit directly acute pancreatitis [111,112]. Conversely, some studies support the involvement of acetaldehyde in both pancreatic fibrosis and carcinogenesis [16,[113][114][115][116][117]. Dysbiotic gut microbiota is able to convert both exogenous and endogenous ethanol to acetaldehyde in a dose-dependent manner [70].…”
Section: Harmful Effects Of Acetaldehyde and Fatty Acid Ethyl Esters mentioning
confidence: 99%